A rare case of Salmonella sp septic arthritis in a patient with systematic lupus erythematosus (SLE) - Steffanus, Mario; Yusuf, Cindy; Hadiyanto, Jessica Novia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Septic arthritis is considered as a medical emergency which can lead to significant morbidity and cause substantial mortality, especially if the diagnosis is delayed. Prolonged use of immunosuppressive and cytotoxic medications as therapy for systemic lupus erythematosus (SLE) causing patient susceptible to secondary infection. However, septic arthritis due to Salmonella sp. is very rare,  makes this is an important extraintestinal manifestation especially in immunosuppressed patients. We presented a case of 25 y.o. female diagnosed with SLE 3 m.o. earlier presented with fever and arthritis on her left genu for 1 wk duration. Genu ultrasonography showed synovitis genu sinistra with fluid volume of 1-2 cc on recessus lateral genu sinistra. The patient was further analysis on her synovial fluid was conducted, the gram stained smear of the fluid showed >25 leucocytes, low power field, and Salmonella sp. was isolated from her synovial fluid analysis. The patient was given intravenous ciprofloxacin and discharged home well. Septic arthritis should always be considered in any patients on long-term immunosuppression state who present with acutely swollen joints. It considered as an important medical emergency with high mortality and morbidity. Hence, prompt recognition, joint aspiration with administration of systemic antibiotics and appropriate surgical intervention plays a pivotal role to minimize morbidity and mortality.